Tionghoa and Environmental Conservation: Between Confucianism and Materialism - ., Sujadmi; Wisadirana, Darsono; Lukman Hakim, M.; Ibrahim, Ibrahim (KnE Social Sciences, 2024)
The Bangka Tionghoa are a group of Tionghoa ethnic descendants who were originally brought to Bangka Island to work as tin miners. The initial arrival of this ethnic group was devoted to increasing tin production on Bangka Island. This study aims to examine the relationship between ethnic Tionghoa and efforts to preserve the environment on Bangka Island. The research method used is a qualitative method with an intrinsic case study design. The number of informants in this study amounted to seven, with the technique of selecting informants by purposive sampling. Data analysis was carried out using the Miles Huberman technique, which included data collection, presentation, and interpretation, as well as drawing conclusions. The perspective used is the choice of rationality put forward by James S. Coleman. Coleman argued that in a social system, individuals play an important role in interventions to create social change. There are two main elements in Coleman’s ideas: actors and resources. The results of the study show that the Bangka Tionghoa ethnic group’s efforts to preserve the environment are based on a rational choice to protect natural resources. Resources that will continue to support their economic lives. The choice made by the Bangka Tionghoa ethnic group to preserve the environment was also influenced by the Confucian values passed down from their ancestors. The existence of supporting actors and resources has made the Bangka Tionghoa ethnic group, whose livelihood is mining, participate in efforts to preserve the environment in order to create sustainable economic resources. Keywords: Confucian values, Tionghoa ethnicity, rational choice